Effects of Blanching and Natural Convection Solar Drying on Quality Characteristics of Red Pepper (Capsicum annuum L.) - James Owusu-Kwarteng; Francis K. K. Kori; Fortune Akabanda (International Journal of Food Science)
The objective of this work was to determine the effects of blanching and two drying methods, open-sun drying and natural convection solar drying, on the quality characteristics of red pepper. A 2 × 3 factorial design with experimental factors as 2 drying methods (open-sun drying and use of solar dryer) and 3 levels of pepper blanching (unblanched, blanched in plain water, and blanched in 2% NaCl) was conducted. Dried pepper samples were analysed for chemical composition, microbial load, and consumer sensory acceptability. Blanching of pepper in 2% NaCl solution followed by drying in a natural convection solar dryer reduced drying time by 15 hours. Similarly, a combination of blanching and drying in the solar dryer improved microbial quality of dried pepper. However, blanching and drying processes resulted in reduction in nutrients such as vitamin C and minerals content of pepper. Blanching followed by drying in natural convection solar dryer had the highest consumer acceptability scores for colour and overall acceptability, while texture and aroma were not significantly (p>0.05) affected by the different treatments. Therefore, natural convection solar dryer can be used to dry pepper with acceptable microbial and sensory qualities, as an alternative to open-sun drying.